STUDY ON WEAR RELIABILITY OF SYNCHRONIZER SLIDERS OF THE TRACKED VEHICLE - AN Hai; ZHOU Ling; YAN ZhaoYi; SUN Peng (Jixie qiangdu)
For wear-out failure problem of synchronizer sliders in the tracked vehicle,the wear experiment and reliability estimation are developed to study in the paper. Firstly,Partial Least Squares（ PLS） Algorithm is used to process the test data and fit the mathematical expression between the wear rate and the influencing factors. The wear safety margin equation of slider is established based on the above expression. Moreover,a new hybrid reliability model and its convergence iteration algorithm are proposed based on the case that truncated random variables,fuzzy random variables,and interval variables are coexisting is studied. Finally,the example of wear reliability of synchronizer slider shows that the good convergence results can be obtained by the iterative algorithm,the hybrid reliability index has better adaptability,wear hybrid reliability index declines with the increase of the number of gear shifting. The approach proposed in the paper also provides a reference for the wear-resisting reliability design of synchronizer slider as well as giving the time of preventive maintenance.